New developments in copyright protection : international harmonization of copyright legislation and the digital agenda. - LIEDES, Jukka (1996)
Discusses the work of the World Intellectual Property Organisation (WIPO) in order to update the international regime of copyright and neighbouring rights. Examine issues relating to the impact of technological developments on copyright, especially the development of the information superhighways.